CLINICAL MANIFESTATIONS OF IMMUNOPATHOLOGY AS A RISK FACTOR OF TUBERCULOSIS IN CHILDREN INCASE OF THE SINGLE INFECTION AND CONCURRENT HIV INFECTION - S. N. Shugаevа; A. G. Petrovа (Туберкулез и болезни лёгких)
In order to detect tuberculosis risk factors among clinical manifestations of immunopathology, a retrospective study was conducted among 177 children (55 children with tuberculous infection only, 50 children with concurrent HIV, and 72 healthy children). The predictive significance of infectious immunopathology syndrome was identified, this syndrome was registered in the major part of children infected with tuberculous infection (40%, OR=6.3) and in all children with TB/HIV co-infection. The following risk factors of developing active disease in case of tuberculous infection were identified: recurrent pneumonias (20%, OR=17.8) and relapsing bronchitis (38.3%, OR=6.8). And the history of clinical manifestations of infectious, lymphoproliferative and autoimmune immunopathology syndromes in the children ill with tuberculosis can be the indirect evidence of concurrent HIV infection.